FAKTOR - FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 - Vina Anggraeny, (2021)
This study aims to test the influence of Firm Size, Profitability (ROE), Capital Structure (DER) and Dividend Policy (DPR) on Company Value (Tobins Q) on LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2019. The data used in this study was obtained from the annual report data. The population in this study was an LQ45 company registered with idx. The sample selection technique used was purposive sampling and obtained by 23 LQ45 companies with a research period in 2015-2019. The data analysis method in this study is multiple linear regression analysis using SPSS software version 25. The results showed that simultaneously Firm Size, Profitability (ROE), Capital Structure (DER), and Dividend Policy (DPR) have a significant effect on the Company's Value (Tobins Q). In part, Firm Size has a negative and significant effect on Company Value (Tobins Q). Profitability (ROE) and Dividend Policy (DPR) have a positive and significant effect on the Company's Value (Tobins Q). While the Capital Structure (DER) has no effect on the Company's Value (Tobins Q).